Development of Teaching Materials Based on Fullan's Deep Learning Framework to Improve the Creative Thinking of Grade VI Elementary Students in Palopo City - Putri, Iin Dwi Aristy; Akib, Erwin; Munirah, Munirah (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study aims to develop teaching materials based on the pedagogical framework of Deep Learning. In the era of globalization and the industrial revolution 4.0, creative thinking as a 21st century skill is crucial, but students experience a